Determinan Peringkat Sukuk: Ditinjau dari Aspek Akuntansi dan Non-Akuntansi - Sofyan Hadinata (Universitas Negeri Padang, 2020)
The objective of this study was to provide empirical findings whether firm size, liquidity, productivity, and sukuk maturity have a significant influence on sukuk ratings. This study uses secondary data. The population of this research is companies issuing sukuk, listed on The Indonesia Stock Exchange and rated by PT PEFINDO. The sampling method used was purposive sampling. Meanwhile, for data analysis this study uses panel data regression method with the assistance of Eviews 10 software. Based on analysis, the results of this study indicate that company size, liquidity, profitability, and productivity have a positive effect on the sukuk rating, while sukuk maturity has a negative effect on the sukuk rating. Several implications of the results of this study. First, sukuk investors will be helped by sukuk rating information, because it reflects the company's financial condition. Second, companies that will issue sukuk or existing sukuk issuers must always put concern on the financial condition of their companies to ensure that the sukuk issued have a good rating. Third, the sukuk issuer must have careful planning to determine sukuk maturity, because it is associated with risks. Fourth, to reduce information asymmetry, policymakers should require all sukuk issuers to rate their sukuk. Keywords: Sukuk Ratings; Company Size; Liquidity; Profitability; Productivity; and Sukuk Maturity